2016
DOI: 10.1177/1029864916684193
|View full text |Cite
|
Sign up to set email alerts
|

Experiential (informal/non-formal) practice does not improve sight-reading skills

Abstract: This study investigates whether experiential (informal/non-formal) sight-reading practice has an impact on sight-reading skills of classical university-level pianists. Data collected from 80 self-report practice diaries of students participating in trials of new sight-reading pedagogies were analysed to evaluate the effect of experiential sight-reading practice on improvement in sight-reading performance, focusing on the overall duration of sight-reading activities accumulated over the 10-week period and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
6
0
5
Order By: Relevance
“…Considering all these studies, it may be suggested that (a) practice SR related skills could be considered as one of the main predictors of SR performance (but see for a different account: Mishra, 2014; Zhukov, 2017); (b) WM processes seem to be involved in SR performance both among expert musicians and those with different levels of instrument knowledge; and (c) regardless of effect of practice, WM could play a role in SR performance, both in rhythm accuracy and in global subjective performance, but the influence of WM is complex and probably depends on the type of indexes of SR performance obtained, or on the kind of WM task used (Kopiez and Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considering all these studies, it may be suggested that (a) practice SR related skills could be considered as one of the main predictors of SR performance (but see for a different account: Mishra, 2014; Zhukov, 2017); (b) WM processes seem to be involved in SR performance both among expert musicians and those with different levels of instrument knowledge; and (c) regardless of effect of practice, WM could play a role in SR performance, both in rhythm accuracy and in global subjective performance, but the influence of WM is complex and probably depends on the type of indexes of SR performance obtained, or on the kind of WM task used (Kopiez and Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have been confirmed by Zhukov et al ( 9 ) who implemented a hybrid approach to SR training that included rhythm training, familiarity with different musical styles, and ensemble work combined into a new curriculum for higher education. In a separate study the entrenched myth that informal practice improves sight-reading was also debunked ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The question of how to improve SR skills and prepare music students for portfolio careers is still being debated. For example, typical approaches to improving SR by practicing have been debunked (Zhukov, 2017), while research-based SR pedagogy that includes rhythm training, experience of different styles, and ensemble playing is showing promising results (Zhukov, Viney, Riddle, Teniswood-Harvey, & Fujimura, 2016).…”
Section: Introductionmentioning
confidence: 99%